The Role of Strategic Partnership in Investigation Organizational Success an Analytical Study of the Opinions of a Sample of Employees Working in a Men’s Clothing Factory in Najaf Governorate - AL-Janabi, Mohanad Abdulabbas Jasim (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The current research aims to study) The role of strategic partnership in enhancing organizational success) In the men's clothing factory in Najaf Al-Ashraf, to achieve the purposes of the research, 85 questionnaires were distributed to a random sample of the employees of the clothing factory in Al-Najaf Al-Ashraf Governorate, and 80 questionnaires suitable for analysis were retrieved, and the statistical program was used. Spss v.26 and AMOS v.26 data analysis program. The results showed a strong correlation between the variable the strategic partnership, its dimensions and the organizational success required in the men is clothing factory in Najaf Al-Ashraf. The practical results also showed that there is a significant impact of the strategic partnership in achieving organizational success. The conclusion was reached that the strategic partnership has a significant impact on organizational success, as the strategic partnership contributes to improving success. One of the important recommendations is that the clothing factory must focus on strategic partnership in order to achieve organizational success.